1999
DOI: 10.1021/jm990165m
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Dmt-Tic Pharmacophore:  Hydrophobic Substituents at the C-Terminus Endow δ Antagonists To Manifest μ Agonism or μ Antagonism

Abstract: Twenty N- and/or C-modified Dmt-Tic analogues yielded similar K(i) values with either [(3)H]DPDPE (delta(1) agonist) or [(3)H]N, N(Me)(2)-Dmt-Tic-OH (delta antagonist). N-Methylation enhanced delta antagonism while N-piperidine-1-yl, N-pyrrolidine-1-yl, and N-pyrrole-1-yl were detrimental. Dmt-Tic-X (X = -NHNH(2), -NHCH(3), -NH-1-adamantyl, -NH-tBu, -NH-5-tetrazolyl) had high delta affinities (K(i) = 0.16 to 1 nM) with variable mu affinities to yield nonselective or weakly mu-selective analogues. N, N-(Me)(2)D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 58 publications
5
81
1
Order By: Relevance
“…56 The benzylamide peptide, H-Dmt-Tic-Gly-NH-CH 2 -Ph, was also found to be a potent agonist (pEC 50 = 8.57) and ␦ antagonist (pA2 = 9.25) in the smooth muscle assays. 28 The heteroaryl analog, H-Dmt-Tic-NH-CH 2 -Bid (Bid = 1 H -benzimidazole-2-yl) similarly displayed potent ␦ antagonist activity coupled with weak agonist activity.…”
Section: E122mentioning
confidence: 97%
See 1 more Smart Citation
“…56 The benzylamide peptide, H-Dmt-Tic-Gly-NH-CH 2 -Ph, was also found to be a potent agonist (pEC 50 = 8.57) and ␦ antagonist (pA2 = 9.25) in the smooth muscle assays. 28 The heteroaryl analog, H-Dmt-Tic-NH-CH 2 -Bid (Bid = 1 H -benzimidazole-2-yl) similarly displayed potent ␦ antagonist activity coupled with weak agonist activity.…”
Section: E122mentioning
confidence: 97%
“…55 Among N-and C-modifi ed Dmt-Tic analogs, the N,N-dimethylated adamantylamide, N,N -(Me 2 )Dmt-Tic-NH-1-adamantane, was found to display high affi nity binding to ␦ and receptors ( K i at ␦ = 0.16 nM, K i at = 1.12 nM) with potent ␦ antagonist (pA 2 = 9.06 in MVD) and agonist (IC 50 = 16 nM in GPI) activities. 56 The benzylamide peptide, H-Dmt-Tic-Gly-NH-CH 2 -Ph, was also found to be a potent agonist (pEC 50 = 8.57) and ␦ antagonist (pA2 = 9.25) in the smooth muscle assays. 28 The heteroaryl analog, H-Dmt-Tic-NH-CH 2 -Bid (Bid = 1 H -benzimidazole-2-yl) similarly displayed potent ␦ antagonist activity coupled with weak agonist activity.…”
Section: Peptide Ligands Possessing Mixed Agonist/ ␦ Antagonist Activitymentioning
confidence: 97%
“…The dipeptide analog H-Dmt-Tic-NH-(CH 2 ) 3 -Ph is also a potent MOPr agonist/DOPr antagonist with subnanomolar MOPr and DOPr binding affinities. Subsequently, the dipeptide derivative Dmt(NMe 2 )-Tic-NH-1-adamantane (Salvadori et al, 1999) and the tripeptide analog H-Dmt-Tic-Gly-NH-CH 2 -Ph (Balboni et al, 2002a) were also reported to be potent MOPr agonists/DOPr antagonists. .…”
Section: Mixed M-opioid Receptor Agonists/d-opioid Receptor Antagomentioning
confidence: 99%
“…Tic-deltorphin was obtained by solid-phase synthesis carried out on an Applied Biosystems 433A peptide synthesizer by using 9-fluorenylmethoxycarbonyl chemistry. N,N-(CH3) 2 -Dmt-Tic-NH 2 was synthesized as reported in Salvadori et al (1999). All materials for tissue culture were supplied by Invitrogen (Paisley, UK).…”
mentioning
confidence: 99%